A thermally erasable silicon oxide layer for molecular beam epitaxy. (20th October 2022) - Hou, Yaonan; Jia, Hui; Tang, Mingchu; Mosberg, Aleksander Buseth; Ramasse, Quentin M; Skandalos, Ilias; Noori, Yasir; Yang, Junjie; Liu, Huiyun; Seeds, Alwyn; Gardes, Frederic
Abstract: We present a systematic study of the oxidation and deoxidation behaviours of several kinds of ultrathin silicon oxide layers frequently used in silicon (Si) technology, which in this work serve as surface protecting layers for molecular beam epitaxy (MBE). With various characterization techniques, we demonstrate that a chemically grown silicon oxide layer is the most promising candidate for subsequent removal in an ultra-high vacuum chamber at a temperature of 1000 ∘ C, without making use of a reducing agent. As a demonstration, a tensile-strained Ge(100) layer is epitaxially grown on the deoxidised wafer with an atomically flat surface and a low threading dislocation density of 3.33 × 10 8 cm −2 . Our findings reveal that the ultra-thin oxide layer grown using a chemical approach is able to protect Si surfaces for subsequent MBE growth of Ge. This approach is promising for the growth of III/V-on-Si (using Ge as a buffer) and all group-IV related epitaxy for integration on the Si photonics platforms.